Il passo dal pensiero alla lingua – l’analisi cognitiva della strada nella lingua italiana - Kosz, Aleksandra (Neophilologica, 2008)
The following paper investigates a cognitive study of strada (way) in Italian. It is an attempt to present the relation between cognitive processes and language on the basis of the chosen concept. A cognitive analysis shows the way of its comprehension. It is a search for the answer to the following question: how do the human perceptive and cognitive processes function and how does the perception of reality influence the language? The analysis of usage of strada presents the linguistic image of the examined concept in Italian. There is an enormous number of relations among the way of perceiving reality, the way of conceiving it, and the way of its interpretation resulting in the linguistic structures. The relation between the process of cognition and the language is undeniable, and this study is an endeavour to reveal the phenomenon observable in use of language, namely the way people project the real world into the abstract one, in order to understand it better and more fully.